GESTIÓN AMBIENTAL EN LA UNIVERSIDAD. HACIA UN DESARROLLO SOSTENIBLE - Bustamante Sánchez, Yolanda (2009)
We are facing a lot of problems such as the climate change, contamination of water, soil and air; the destruction of the forest, the reduction of the ozone layer, emission of gases that affect human beings survival. In this context, arises the University, as a referent to undertake sustainable actions that protect the environment for today’s world and the coming generation.